Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7150/ijbs.58295
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase 3 dysfunction promotes tumorigenesis and immune escape by upregulating monocyte/macrophage infiltration into the clear cell renal cell carcinoma microenvironment

Abstract: Purpose: This study aimed to identify the potential prognostic role of HK3 and provide clues about glycolysis and the microenvironmental characteristics of ccRCC. Methods: Based on the Cancer Genome Atlas (TCGA, n = 533) and Gene expression omnibus (GEO) (n = 127) databases, real-world (n = 377) ccRCC cohorts, and approximately 15,000 cancer samples, the prognostic value and immune implications of HK3 were identified. The functional effects of HK3 in cc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“… 12 Moreover, several studies have reported that macrophages, Tregs, and CD8+ T cells in the KIRC microenvironment can promote tumour growth and immune escape. 39–41 These results suggest that DLEU2 may influence the prognosis of KIRC and LIHC by regulating immune cell infiltration in the TME.…”
Section: Discussionmentioning
confidence: 80%
“… 12 Moreover, several studies have reported that macrophages, Tregs, and CD8+ T cells in the KIRC microenvironment can promote tumour growth and immune escape. 39–41 These results suggest that DLEU2 may influence the prognosis of KIRC and LIHC by regulating immune cell infiltration in the TME.…”
Section: Discussionmentioning
confidence: 80%
“…We also found that positive regulation of voltage-gated potassium channel activity is related to LGG. MicroRNAs (miRNAs) can reportedly promote the development of invasive nonfunctional pituitary adenomas (74,75). Current knowledge suggests that voltage-gated potassium channels play a fundamental role in the generation and transmission of action potential ( 76), but their role in tumors has not been deeply studied.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have shown that tumor metastasis and invasion are inseparable from the microenvironment and purity of tumor cells (36). A comprehensive analysis of the role of TME in ccRCC helps to identify the tumor immunophenotype of ccRCC, explores independent prognostic indicators and novel therapeutic targets, thereby improving the prognosis of patients and the ability to predict the effect of immunotherapy (37)(38)(39). Studies have shown that tumor purity of TME is significantly related to the clinical characteristics, genome expression, and biological characteristics of tumor patients.…”
Section: Discussionmentioning
confidence: 99%